Elk Island National Park of Canada : management plan ... - Kanada - Parks (2005)
Every national park in Canada has a management plan that provides a long-term vision and strategic direction for the park. Management plans are reviewed every five years, with input and involvement from partners, stakeholders and the public, to ensure that the plan remains valid and effective